In Vitro Detection of Acaricidal Resistance Status of Rhipicephalus (Boophilus) microplus against Commercial Preparation of Deltamethrin in Coastal Areas of South Gujarat, India - Patel, Dharmesh C; Solanki, Jayesh B; Kumar, Niranjan (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A total of 2617 bovines (1682 cattle and 935 buffaloes) of coastal districts (Bharuch, Surat, Navsari and Valsad) of South Gujarat were  screened for tick Rhipicephalus (Boophilus) microplus, the most economically important ectoparasite of bovines worldwide. Farmers  chiefly relied on chemical acaricides (67.52%) to kill the ticks, and under chemical method 44.09, 24.17, 30.50 and 1.24 % animals had  received cypermethrin, deltamethrin, ivermectin and fipronil, respectively, thus favouring the resistance. In adult immersion test (AIT),  the median lethal concentration (LC50) was 144.23, 93.97, 141.67 and 57.89 ppm for deltamethrin in Bharuch, Surat, Navsari and Valsad  district, respectively. Resistance level was I in Valsad and II in other 3 districts for deltamethrin in AIT. In larval packet test (LPT), the  median LC50 was 297.29, 126.81, 127.83 and 93.92 ppm for deltamethrin in Bharuch, Surat, Navsari and Valsad district, respectively.  Resistance level was III in Bharuch and II in other district in LPT.
Keywords: Acaricide; Deltamethrin; Rhipicephalus (Boophilus) microplus; Resistance; South Gujarat